A Legal Review of PayLater based on Law Number 4 of 2023 on The Development and Strengthening of The Financial Sector - Selvi Novia Safitri; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2025)
Developments in the financial technology (FinTech) sector have given rise to various innovations in payment systems, one of which is the PayLater service which allows consumers to make purchases with payments that can be postponed. The aim of this research is to analyze legal regulations related to PayLater services based on Law Number 4 of 2023 concerning Development and Strengthening of the Financial Sector (UU P2SK) as well as legal protection efforts for consumers. With a normative legal research approach, and a type of descriptive research that uses secondary data. Primary legal materials in the form of the P2SK Law as the legal basis for PayLater services, which involves supervision by the Financial Services Authority (OJK), tertiary legal materials in the form of journals, books and other sources as reinforcement for primary legal materials. And finally, tertiary legal material in the form of a large Indonesian dictionary as a guide for writing this research. The results of this research are to find out the legal regulations related to Paylater based on Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector and secondly to find out consumer protection for Paylater users according to the regulations of Law Number 4 of 2023.